Views on the Roles of Non-Native English Speaker Teachers Compared to Their Native Counterparts: Indonesian Context - Solihin; Aris Dwi Intan Aprianti (Hasanuddin University, 2022)
The presence of Native English Speaker Teachers (NESTs) in a number of English courses, formal schools and universities has sparked debates among Non-Native English Speaker Teachers (NNSTs) in Indonesia. Some practitioners believe that the involvement of NESTs in education institutions brings about more benefits to their students and institutions than solely hiring NNESTs. However, some others believe that NNESTs are not less superior to their NEST counterparts. This study evaluated these beliefs by looking at the concerns about NNESTs compared to NESTs in the context of Indonesia. The data in this study were obtained from a number of related literatures. Supporting data were obtained through participant observation during the authors’ training in education institutions that involved NESTs and by finding out the views of a university chairman who earned his masters and doctorate degrees in an English Speaking country. Besides, data were collected through an interview with three Australian university graduates who were taught by NNESTs in their secondary (junior and senior high schools) education and trained by NESTs prior to their departure to Australia for pursuing their masters degrees. In the final part, the results of this research indicate that NNESTs still deserve to have the same opportunity as NESTs. The findings, however, also suggest that the contexts in which NESTs and NNESTs are most effective differ.